Stressors and Coping Strategies for Junior College Students in Maritime Boarding College - Fitri Zuhriyah; Mulya Virgonita I. Winta; Margaretha Maria Shinta Pratiwi (Dinamika Bahari, 2023)
One of the challenges encountered by the first year students of boarding universities is having a transition period for adapting to the needs and requirements in their new environments. Inability to make a self-adaptation can lead to unbalanced situation that results in academic, environmental, and interpersonal relationship problems as well as inner-self problems of the individuals. This study is aimed at closely viewing the stressors experienced by the students in the first year of their study, particularly during the first three months of their lives in the new environments and knowing the strategies taken by the individuals to encounter the stressors in order to anticipate the possible effects in the near future. The method used in this research is qualitative with a descriptive approach for exploring or depicting the images of stressors encountered by the students in the first three months of living in a boarding house and how they determine the coping to encounter the stressors. The results show that the stressors experienced by the students consisted of intrapersonal stressors (62.59%), interpersonal stressors (17.65%), environmental stressors (14.35%), and academic stressors (5.41%). The students tend to face the stressors by focusing on the problems (53.17%) and the emotions (46.38%). Based on the findings, it can be concluded that the mist dominant stressor is the one that is related to the students' individuals.